Analisis Kontribusi Sektor Pertanian dan Sumber Daya Hayati Non-Pertanian terhadap Pertumbuhan Ekonomi Wilayah di Kota Depok - Chairunnissa Putri; Johan Setiawan; Setiawan Sariyoga (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to analyze the influence of the agricultural and non-agricultural sectors on regional economic growth in Depok City during the 2020–2024 period. Although agricultural land area has declined to 157.42 hectares in 2024, this sector exhibits a paradoxical phenomenon in the form of an increasing growth rate, thereby necessitating a strategic evaluation of its development potential. Using Gross Regional Domestic Product (GRDP) data, this study applies the Location Quotient (LQ), Basic Service Ratio (BSR), Regional Investment Multiplier (RIM), Shift Share, and Klassen Typology methods. The results indicate that the economy of Depok City is driven by ten base sectors, including construction, trade, and financial services. Although the agricultural sector is classified as a non-base sector with an average LQ value of 0.50, it falls into the category of a potential sector in Quadrant III of the Klassen Typology due to its growth rate of 17.76 percent, which significantly exceeds the average growth rate of the reference region. Furthermore, a BSR value of 1.70 and an RIM value of 1.58 indicate that each one-unit increase in growth in the base sector is able to generate a substantial stimulus to non-base sector activities as well as an overall increase in regional income. This study concludes that despite the ongoing process of economic modernization, the agricultural sector in Depok City remains competitive.